1998
DOI: 10.1007/bf03161876
|View full text |Cite
|
Sign up to set email alerts
|

Dissymmetrization in X-irradiated RbTiOPO4 crystal

Abstract: Electron paramagnetic resonance has been used to study the hole and electron paramagnetic centers formed in X-irradiated RbTiOPO4, the crystals of the KTP family. X-irradiation of RbTiOPO4 crystals at 77 K produced an oxygen hole center and four different trivalent titanium electron centers I" II, III and IV. The g-tensors, their principal values and axes for the defects were calculated and compared with those for KTiOPO4 centers. X-irradiation at 300 K produced another two oxygen hole centers and three electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2005
2005
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
(26 reference statements)
1
8
1
Order By: Relevance
“…Thus, we agree with Laruhin et al [18] that the dominant trapped hole center formed in RTP by exposure to ionizing radiation at 77 K is associated with a rubidium vacancy, but we significantly modify the initial interpretation of the hyperfine structure that they offer.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…Thus, we agree with Laruhin et al [18] that the dominant trapped hole center formed in RTP by exposure to ionizing radiation at 77 K is associated with a rubidium vacancy, but we significantly modify the initial interpretation of the hyperfine structure that they offer.…”
supporting
confidence: 89%
“…In the present paper, we describe the results of an EPR and ENDOR study of the dominant trapped hole center initially reported by Laruhin et al [18] in RTP crystals. This defect is produced in RTP by © 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim irradiating at 77 K with X-rays.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations